2018
DOI: 10.2478/cait-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Fast Walsh Transform Algorithm and Its Implementation with CUDA on GPUs

Abstract: Some of the most important cryptographic characteristics of the Boolean and vector Boolean functions (nonlinearity, autocorrelation, differential uniformity) are connected with the Walsh spectrum. In this paper, we present several algorithms for computing the Walsh spectrum implemented in CUDA for parallel execution on GPU. They are based on the most popular sequential algorithm. The algorithms differ in the complexity of implementations, resources used, optimization strategies and techniques. In the end, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…They also concluded that implementation was not suitable for large S-Boxes in terms of time and memory and suggested use of parallelization for solving this problem. Bikov et al (2018) parallelized the walsh spectrum of boolean functions by using fast walsh al. in alternative ways, running them on GPU, and finally, comparing the results [15].…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…They also concluded that implementation was not suitable for large S-Boxes in terms of time and memory and suggested use of parallelization for solving this problem. Bikov et al (2018) parallelized the walsh spectrum of boolean functions by using fast walsh al. in alternative ways, running them on GPU, and finally, comparing the results [15].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Bikov et al (2018) parallelized the walsh spectrum of boolean functions by using fast walsh al. in alternative ways, running them on GPU, and finally, comparing the results [15]. Various parallelization of fast walsh al.…”
Section: Research Backgroundmentioning
confidence: 99%
“…For the programs we have used GPU computing model with CUDA. This allows us to interact directly with the GPUs and run programs on them, thus effectively utilizing the advantages of parallelization (many details about the parallel algorithms and programs are given in [2]). For this research, we have used a graphic card NVIDIA GeForce Titan X Pascal which we have as a donation from NVIDIA Corporation.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithms that use listings of codewords, are faster for small lengths because they use bitwise representation of the codewords and bitwise operations. For larger lengths, the algorithms close to discrete Fourier transforms, can be represented by a butterfly diagram and are therefore suitable for parallelization [4].…”
Section: Introductionmentioning
confidence: 99%